The results of the Initial Feasibility Program on cavitation descaling techniques for pipes and tubes used in geothermal energy plants - United States. Department of Energy. (Daedalean Associates, Inc., 1978)
Since 1970, increasing national attention has been focused on the potential of using geothermal resources for electrical power generation. Significant amounts of electric power produced from geothermal steam (790 megawatts as of 1972) have been generated in various countries throughout the world including the US, italy, New Zealand, iceland, japan, Mexico, and the Soviet Union. Commercial geothermal development in the US has centered in northern California (Geysers), and in southern California (Imperial Valley). A combination of the Magma Power Co., the Union Oil Col, and the Thermal Power Co., has been drilling geothermal wells and producing steam in northern California since 1960. The pacific Gas and Electric Co. purchases the steam for the generation of electricity. The Imperial Valley is a wet steam geothermal resource area currently being considered by major oil companies and electrical utilities for commercial geothermal exploitation. This valley is one of approximately 1,000 geothermal hot water systems presently identified in the US. A recent survey has determined that the total power potential in the US from geothermal hot water systems is between 1 million and 10 million megawatts, with an associated resource life estimated between 100 and 300 years.